Estrategias lúdicas para mejorar el razonamiento lógico matemático - Cargua Palomo, Ana Maribel (2018)
For generations, games have been the basis of education of humans, it allows conveying rules of social coexistence. Those games will foster the interest and enthusiasm for math since that games stimulate and encourage to the students to take an active role in the learning process, being creative and spontaneous. Once the research was carried out at '' Pelileo '' school, it has been detected great amount of students have problems to development of logical thinking in the math stream. Which raises to look for solutions. As conclusion, by means of the playful strategies, traditional methodology will be left aside, better results can be obtained. It is important that the choice be based on realistic criteria and in a balanced way, in the way that can be positive not only for students who behold difficulties in learning process, but for the all the students whom are involve in learning. The present research project is based on the qualitative approach, because it seeks to explain a reality of the playful strategies to improve the Math Logical thinking used Basic Education career through the collection of data to be interpreted and determine the existing problem. The techniques used were interviews and surveys which allowed collecting information from teachers and students involve in this situation. For that reason, it is necessary to apply the playful strategies to improve their academic success and inters to learn math.